USE OF STORYMAP IN DISASTER MITIGATION BASED ON LOCAL WISDOM (Case Study: Sapuran District, Wonosobo Regency, Central Java) - Dessy Apriyanti; Celine Tracyana; Fauzan Zaidan (Jurnal Mineral, Energi dan Lingkungan, 2024)
Wonosobo, known for its highland topography and significant tourism potential, stands out as a region deeply enriched by local wisdom and strategic location, which has earned it the moniker "The Soul of Java." This branding reflects Wonosobo’s unique cultural and natural attributes, making it an attractive destination with immense tourism potential. However, the region's natural beauty also comes with inherent risks, particularly the threat of natural disasters. The local community's limited education and awareness about these risks highlight the urgent need for an effective educational tool that can reach all societal layers. A promising solution is the development of a Story Map, which can transform complex information into an engaging and accessible format. Story Maps combine maps with narrative text, images, and multimedia elements, making them an effective medium for educating the public. The process begins with collecting detailed information on local wisdom from the Sapuran District, focusing on significant cultural sites and traditions. This information is then carefully filtered to ensure accuracy and relevance. Next, a map is created to visually represent the distribution of these local wisdom sites throughout Wonosobo. This map is integrated into a Story Map, designed to be both visually appealing and interactive. The Story Map not only showcases the rich cultural heritage of the region but also includes crucial information about disaster risks and preparedness. By presenting this information in an engaging format, the Story Map aims to enhance community awareness, promote cultural appreciation, and improve disaster readiness. This approach ensures that residents and visitors alike can access important information in a manner that is both informative and enjoyable, thereby fostering greater resilience and engagement with Wonosobo’s unique heritage.